Multi-Omics Analysis of the Microbiome and Metabolome Reveals the Relationship Between the Gut Microbiota and Wooden Breast Myopathy in Broilers - Kang, Kelang; Zhou, Nanxuan; Peng, Weishi; Peng, Fang; Ma, Mengmeng; Li, Liwei; Fu, Fuyi; Xiang, Shuhan; Zhang, Haihan; He, Xi; Song, Zehe (Frontiers in Veterinary Science, 2022)
Wooden breast (WB) is a widely prevalent myopathy in broiler chickens. However, the role of the gut microbiota in this myopathy remains largely unknown, in particular the regulatory effect of gut microbiota in the modulation of muscle metabolism. Totally, 300 1-day-old Arbor Acres broilers were raised until 49 days and euthanized, and the breast filets were classified as normal (NORM), mild (MILD), or severe wooden breast (SEV). Birds with WB comprised 27.02% of the individuals. Severe WB filets had a greater L* value, a* value, and dripping loss but a lower pH (P < 0.05). WB filets had abundant myofiber fragmentation, with a lower average myofiber caliber and more fibers with a diameter of <20 μm (P < 0.05). The diversity of the intestinal microflora was decreased in birds with severe WB, with decreases in Chao 1, and observed species indices. At the phylum level, birds with severe WB had a lower Firmicutes/Bacteroidetes ratio (P = 0.098) and a decreased abundance of Verrucomicrobia (P < 0.05). At the species level, gut microbiota were positively correlated with 131 digesta metabolites in pathways of glutamine and glutamate metabolism and arginine biosynthesis but were negatively correlated with 30 metabolites in the pathway of tyrosine metabolism. In plasma, WB induced five differentially expressed metabolites (DEMs), including anserine and choline, which were related to the severity of the WB lesion. The microbial-derived metabolites, including guanidoacetic acid, antiarol, and (2E)-decenoyl-ACP, which entered into plasma were related to meat quality traits and myofiber traits. In summary, WB filets differed in gut microbiota, digesta, and plasma metabolites. Gut microbiota respond to the wooden breast myopathy by driving dynamic changes in digesta metabolites that eventually enter the plasma.